Effects of Crystal Phases and Morphology of Aluminum Oxide on the Heterogeneous Catalytic Ozonation Process Using Pyruvic Acid as an Indicator - Song, S.; Jiang, Z.; Jiang, L.Y.; He, Z.Q.; Wu, M.; Sun, J.J.; Chen, J.M. (Asian Journal of Chemistry, 2013)
Aluminum oxide as an efficient heterogeneous catalyst has received much attention in the field of ozonation. In this study, the impact of the instinct properties of Al2O3, including its crystalline phase and morphology, on the ozone-catalytic oxidation process were evaluated. The nanoparticles, nanotubes, nanorods, nanoleaves, nanoflakes and spindle-like 3D nanoarchitectures were constructed via hydrothermal methods and the crystal phases such as g-, d-, q- and a-Al2O3 were controlled by appropriate calcinations using boehmite as precursor. The catalytic activity of the samples was tested by using degradation of pyruvic acid in aqueous solution in the presence of ozone, with a semicontinuous laboratory reactor. The initial degradation rates of pyruvic acid were found to correlate to the number of surface OH groups on the Al2O3. Based on these findings, along with additional information from the techniques transmission electron microscopy, X-ray diffraction and Brunauer-Emmett-Teller measurements, it is concluded that large surface areas and the a-phase of Al2O3 facilitate the degradation of pyruvic acid with ozone. The morphology effects of the catalysts were negligible in present experiments.